2015
DOI: 10.1002/ddr.21236
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Potassium Channels in the Vasodilatation Induced by Resveratrol and Naringenin in Isolated Human Umbilical Vein

Abstract: Preclinical Research Potassium (K ) channels have a key role in the maintenance of smooth muscle tone; a variety of agonists can modify the tone by altering K -channel activity. The aim of this study was assess the effects of the phenols, resveratrol, and naringenin on K -channels of the vascular smooth muscle. Segments of human umbilical vein (HUV) without endothelium were precontracted using serotonin (100 μM) or 100 mM K to derive cumulative concentration-response curves using increasing concentrations of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Also, the effects of resveratrol in vivo may also involve its actions on potassium channels [27,28,29], gut microbiota [30,31], and circadian gene expression [32].…”
Section: Resveratrol and Its Molecular Targetsmentioning
confidence: 99%
“…Also, the effects of resveratrol in vivo may also involve its actions on potassium channels [27,28,29], gut microbiota [30,31], and circadian gene expression [32].…”
Section: Resveratrol and Its Molecular Targetsmentioning
confidence: 99%
“…In addition, RJ is still able to relax the endothelium‐denuded aorta rings, indicating that RJ has a direct relaxation effect on VSMC. Although changes in the K + channel activity of VSMC membranes regulate membrane potential, which is an important mechanism involved in arterial vasoconstriction and vasodilation (Kohler, Kaistha, & Wulff, ; Protic et al, ). However, RJ not only had weak vasodilation effect on the KCl models, and different types of potassium channel blockers also had no effect on RJ’s vasorelaxation (Data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with the data obtained on different blood vessels (rat portal vein, porcine retinal arterioles and human umbilical vein). It has been shown that, without endothelium, the BK Ca channels partly mediate the relaxant effect of RSV (6,7,79). Nevertheless, the results of previous studies show that BK Ca channels were not involved in the relaxant effect of RSV in blood vessels without endothelium-rat aorta, mesenteric artery and in human mammary artery (5,59,77,80,81).…”
Section: Effects Of Resveratrol On the Smooth Muscle K Ca Channelsmentioning
confidence: 97%
“…However, only BK Ca smooth muscle channels were partly involved in the RSV-induced inhibition of neurogenic contractions. Another investigation of the effects of RSV on vein was on human umbilical vein (79). In vitro studies of this endothelium-denuded vein reveal that Kv, K Ca , and Kir channels play important role in the RSV-induced vasodilatation.…”
Section: Effects Of Resveratrol On the Smooth Muscle Potassium Channels In Cardiovascular Systemmentioning
confidence: 99%